Fully automated treatment planning of spinal metastases - a comparison to manual planning of Volumetric Modulated Arc Therapy for conventionally fractionated irradiation - Bürgy, Daniel; Wenz, Frederik; Lohr, Frank; Stieler, Florian (Radiation oncology, 2017)
Planning for Volumetric Modulated Arc Therapy (VMAT) may be time consuming and its use is limited by available staff resources. Automated multicriterial treatment planning can eliminate this bottleneck. We compared automatically created (auto) VMAT plans generated by Erasmus-iCycle to manually created VMAT plans for treatment of spinal metastases.